Training Model To Improve Competency State Civil Apparatus Supervisory Officer - Rita Ningsih; M Juhri AM; Agus Pahrudin; Agus Jatmiko (International Journal of Educational Research & Social Sciences, 2021)
Due to the development of technology and organizational needs, the competence of the State Civil Apparatus has increased significantly, necessitating the adjustment of improvement techniques. Furthermore, the lack of a role for the sending agency in training continues to be an impediment to the intersperity between competence needs and the implementation system. This research focuses on how the competency-based training model is applied, as well as the function and impact of supervisory authorities' training results on enhancing performance. This study uses a combination of qualitative and quantitative methods to obtain results that are relevant to the needs, and it was conducted at the State Administration Agency's Center for Training and Development and Competency Mapping of State Civil Apparatus with alumni research training supervisory officials in 2018, 2019, and 2020. According to the findings of the study, the training has not taken advantage of technological advancements or maximized the role of the sending agency, so there are still difficulties and limits in its execution, particularly in terms of location and time. To meet these issues, a training model must be developed that focuses on ensuring the organizer's competency.